Analysis of cell surface and relative gene expression of heat shock protein 70 in human leukemia cell lines - Hromadnikova, Ilona; Sedlackova, Lucie (Leukemia & lymphoma, 2008)
Hsp70 was found to be expressed on the cell surface of leukemia cell lines compared with normal cells. Hsp70 cell surface and mRNA expression was studied in K562, Jurkat and CCRF-CEM human leukemia cell lines during several passages of in vitro culture. All the cell lines were positive for cell surface Hsp70 expression. However, increased mRNA expression was observed only in K562 cells where the expression was 9.88-fold higher on average compared with healthy controls. Jurkat cells, however, showed a significant negative correlation between cell surface and mRNA Hsp70 expression; high cell surface expression correlated with low mRNA expression in the Jurkat cell line.
Keywords: messenger RNA; membránové proteiny; nádorové buněčné linie; průtoková cytometrie; Membrane Proteins; Jurkat buňky; K562 Cells; polymerázová řetězová reakce; Polymerase Chain Reaction; Antigens, Surface; HSP70 Heat-Shock Proteins; Cell Line, Tumor; buňky K562; Flow Cytometry; antigeny povrchové; RNA, Messenger; Humans; Jurkat Cells; proteiny tepelného šoku HSP70; leukemie; lidé; Leukemia